Hepatitis B-related hepatocellular carcinoma: classification and prognostic model based on programmed cell death genes - Tian, Jinyue; Meng, Jiao; Yang, Zhenkun; Song, Li; Jiang, Xinyi; Zou, Jian (Frontiers in Immunology, 2024)
Hepatitis B virus (HBV) infection is a major risk factor for hepatocellular carcinoma (HCC). Programmed cell death (PCD) is a critical process in suppressing tumor growth, and alterations in PCD-related genes may contribute to the progression of HBV-HCC. In this study, we analyzed 139 HBV-HCC samples from The Cancer Genome Atlas (TCGA) and validated them with 30 samples from the Gene Expression Omnibus (GEO) database. 70 PCD-related genes from three types of PCD, including cuproptosis, netotic cell death, and pyroptosis, were used for clustering. We identified three distinct subgroups of HBV-HCC patients with different clinical characteristics and survival outcomes. Among them, Cluster 2 demonstrated significant activation in DNA replication-related pathways and tumor-related processes. Analysis of copy number variations (CNVs) of PCD-related genes also revealed distinct patterns in the three subgroups, which may be associated with differences in pathway activation and survival outcomes. Based on the PCD-related genes, we developed a prognostic model that incorporates genomic and clinical information and provided novel insights into the molecular heterogeneity of HBV-HCC. In our study, we emphasized the significance of PCD-related genes, particularly DLAT, which was examined in vitro to explore its potential clinical implications. Our findings underscore the importance of immune cell infiltration and the microenvironment in the advancement of HBV-HCC.